Plain language in history museums: a project with wall information - Martins, Cláudia (2022)
The UN Convention on the Rights of Persons with Disabilities has become a watershed for human rights. It enshrines “full and equal enjoyment” for all people with disabilities, namely participation in cultural life (cf. art. 30) which requires the development of accessibility services that may cater for the needs and requirements of specific groups. Among these services, we highlight easy/ plain language as a means to include people with cognitive impairments, or anyone “with communication impairments” (Hansen-Schirra & Maaß, 2020), by both improving “readability and comprehensibility” (ibidem). This is particularly important in cultural venues, e.g. museums, since it can be used by a myriad of visitors, such as children, the elderly, people with lower literacy or simply with less experience going to museums, and people with hearing impairment. However, such strategies may be regarded with suspicion for challenging long-held suppositions that need to be deconstructed by these institutions. Bearing this in mind, we wish to report on a project conducted in a Portuguese museum in Bragança (northeast of Portugal), which goes by the name of Abbott of Baçal Museum. For this history museum, we were asked to adapt 16 texts that would stand as wall information in each of the museum rooms, i.e. adapt them into easy/ plain language. Therefore, our paper aims not only at conducting a contrastive analysis between the original text handed in by the institution and the outcome of the “simplification” process, but also at reflecting on the intralingual translation strategies used to reach quality texts.